Family Role And Religious Moderation Islamic Education Perspective: Millenial Radicalism Prediction - Charles Charles; Yusutria Yusutria; Yuherman Yuherman (STAI Hubbulwathan Duri, 2023)
The role of the millennial generation is very strategic in preventing radicalism. This discussion aims to find out the role of the family in instilling religious moderation from an Islamic education perspective: anticipating radicalism in the millennial generation. This discussion uses a qualitative approach to library research, with primary and secondary data sources. The analytical method used for data validity takes the context into account takes into account the context. This analysis emphasizes the process of seeing the content of communication qualitatively and interpreting the content of communication and the symbolic interactions that occur. Radical spreading factor: political developments, economic inequality, mental health, wrong understanding of religion, intolerance, blind bigotry, exclusive attitude, revolutionary attitude. Against radicalism in the millennial generation: instilling awareness through families, schools and communities of the importance of maintaining unity and oneness, and the role of religious leaders and scholars in providing understanding. The concept of religious moderation in Islam is classified into deep moderation: having faith, worship, behaving, and formation of sharia. Understanding and practising Islamic amaliyah moderation in the family: providing excessive and lacking understanding and practice of religion, balance in understanding and practising religion, putting something in its place and carrying out rights and obligations proportionally, recognising and respecting differences, not discriminatory, solving the problem by way of deliberation, prioritize reformative principles, prioritize priorities, always open to changes according to the times. 10. Uphold good morals.